Study loans for tertiary education - Chua, Li Hong (2014)
The purpose of this report is to determine the preference of tertiary students for study loan features. In addition, the current banks’ marketing strategies with regards to study loans are also examined. Research on the study is focused on comparisons of the study loan schemes from six commercial banks, interviews with bank officers and questionnaires to students.